SAFETY PROFILE OF DIPEPTIDYL PEPTIDASE-4 INHIBITORS - M. Ganeva (Trakia Journal of Sciences)
Dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) are oral antidiabetic agents commonly used for the treatment of type 2 diabetes mellitus. More than ten years of clinical experience with this group of drugs provides evidence of their efficacy and good tolerability especially in patients at risk of hypoglycemia. DPP4 inhibitors act by increasing the levels of the incretins glucagon-like peptide-1 (GLP-1) and glucosedependent insulinotropic peptide (GIP) and thus augmenting glucose-induced insulin secretion. The enzyme DPP-4 degrades plenty of substrates including chemokines, cytokines, and neuropeptides. Thus the inhibition of DPP-4 may affect many biological and pathological processes. Although rarely DPP-4 inhibitors have been reported to induce the development of infections, heart failure, liver injury and pancreatitis. The longterm effects of DPP-4 inhibition on the immune function are still not clarified. The close monitoring of polymorbid patients using DPP-4 inhibitors, and the reporting of possible adverse reactions associated with these drugs is warranted.